2021
DOI: 10.1016/j.ejvs.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

How Does SARS-CoV-2 Infection Affect Survival of Emergency Cardiovascular Patients? A Cohort Study From a German Insurance Claims Database

Abstract: WHAT THIS PAPER ADDSThis large scale analysis of nationwide and unselected health insurance claims data covering 316 718 hospitalisations for cardiovascular and cerebrovascular emergencies between January 2017 and October 2020 in Germany revealed an association between the COVID-19 pandemic and acute stroke and confirmed SARS-CoV-2 infection (for acute stroke, acute limb ischaemia, transient ischaemic attack) led to increased in hospital mortality in patients admitted with cardiovascular and cerebrovascular em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“… 43 Similar findings were also reported by a German study that analysed health insurance claims data, which observed a higher mortality in COVID-19 patients admitted for cardiovascular conditions such as acute stroke, acute limb ischaemia and transient ischaemic attacks. 44 On the contrary, the COVER tier 2 study demonstrated a elevated in-hospital mortality risk across patients who underwent aortic, carotid or lower limb procedures despite a low (4%) COVID-19 infection rate. 40 The authors of the COVER tier 2 study attributed the increase of in-hospital mortality to indirect effects of the COVID-19 pandemic such as delayed presentation, case postponement, increased size threshold for aortic aneurysm repair, and infrastructure change.…”
Section: Resultsmentioning
confidence: 98%
“… 43 Similar findings were also reported by a German study that analysed health insurance claims data, which observed a higher mortality in COVID-19 patients admitted for cardiovascular conditions such as acute stroke, acute limb ischaemia and transient ischaemic attacks. 44 On the contrary, the COVER tier 2 study demonstrated a elevated in-hospital mortality risk across patients who underwent aortic, carotid or lower limb procedures despite a low (4%) COVID-19 infection rate. 40 The authors of the COVER tier 2 study attributed the increase of in-hospital mortality to indirect effects of the COVID-19 pandemic such as delayed presentation, case postponement, increased size threshold for aortic aneurysm repair, and infrastructure change.…”
Section: Resultsmentioning
confidence: 98%
“…When comparing ALI in patients with COVID-19 (2.4%) with those who were not infected, a higher in hospital mortality was observed (14.3% vs. 5.0%, p < .001). 57…”
Section: Outcomes After Treatmentmentioning
confidence: 99%
“…Hinsichtlich der Versorgung zeigte eine retrospektive Studie der BARMER Krankenkasse [20], dass die Pandemie die Schlaganfall-Versorgung negativ beeinflusst. So gab es während der ersten Pandemie-Welle im Vergleich zum Vorjahr 9 % weniger Schlaganfall-bedingte Hospitalisierungen und 15 % weniger TIAs.…”
Section: Neurovaskuläre Manifestationen Bei Covid-19unclassified